Grammar Reframing: Mobile-Based Instruction’s Impact on Student Perception and Performance - Dewa Gede Agung Gana Kumara (Indonesian Journal of Foreign Language Studies, 2025)
Teaching English grammar remains a significant challenge in language education, with ongoing debates about effective instructional methods. This mixed-methods study investigates the impact of Mobile-Based Instruction (MBI) on students’ perceptions and performance in English grammar courses. Twenty-five intermediate-level learners participated, completing pre-tests, post-tests, questionnaires, and interviews. Quantitative results showed a 20% improvement in grammar knowledge, while qualitative data revealed increased motivation and positive attitudes toward grammar learning following the MBI intervention. These findings suggest that integrating mobile technology with traditional teaching methods enhances both understanding and engagement. This study contributes to the growing body of research on technology-enhanced language learning and offers practical insights for educators seeking to modernize grammar instruction.